1986
DOI: 10.1200/jco.1986.4.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Serial levels of CA 19-9 and CEA in colonic cancer.

Abstract: The use of serial carbohydrate antigen (CA) 19-9 assays was assessed by comparison with serial carcino-embryonic antigen (CEA) levels on the plasmas of 53 patients with colorectal carcinoma. The patients had all undergone resection for their primary tumors and in six instances subsequent resections for hepatic metastases. Initial CA 19-9 levels were greater than or equal to 37 U/mL in 22 of the 53 patients (41%) and in 68% of the patients with metastatic disease. Similar trends of serial CA 19-9 and CEA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…The CA19-9 assay detects a mucin containing a pentasaccharide epitope (fucopentaose II) considered to be a tumor marker in pancreatic adenocarcinoma [25]. Abnormal CA19-9 serum levels were also found in patients with cholangiocarcinoma [26], colorectal cancer [27], gastric cancer [28], and a wide range of benign conditions, such as liver diseases, ascending cholangitis, and pancreatitis [29]. The preoperative CA19-9 level has been reported to be a prognostic factor for pancreatic cancer [30] and cholangiocarcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…The CA19-9 assay detects a mucin containing a pentasaccharide epitope (fucopentaose II) considered to be a tumor marker in pancreatic adenocarcinoma [25]. Abnormal CA19-9 serum levels were also found in patients with cholangiocarcinoma [26], colorectal cancer [27], gastric cancer [28], and a wide range of benign conditions, such as liver diseases, ascending cholangitis, and pancreatitis [29]. The preoperative CA19-9 level has been reported to be a prognostic factor for pancreatic cancer [30] and cholangiocarcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum CA 19-9 levels can be found in various gastrointestinal cancers, including gastric cancer, pancreatic cancer, colorectal cancer etcetera. [20][21][22] As for ascitic fluid CA 19-9, Mezger et al reported that determination of CA 19-9 in ascites, at a cut-off level of 30 U/mL, was specific (1 00%) but not sensitive (52%) enough in the diagnosis of malignancy-related ascites.2 Our series showed a better result, 65.5% sensitivity and 93.6% specificity, with a cut-off level of 50 U/mL. The assessment of CA 19-9 assay in the current study, though highly specific, is still not sensitive enough.…”
Section: Discussionmentioning
confidence: 99%
“…In our group’s NV1020 trial, all patients experienced partial response and CEA reduction following viral and chemotherapy, and the patient with the greatest radiographic tumor reduction in response to one dose of virus alone (39%) also had the greatest reduction of CEA level (75%) (17;21). While CEA levels vary greatly between patients, relative change in CEA in a single patient has been correlated with tumor recurrence and tumor burden (8083). Accordingly, CEA could serve as a marker for oHSV efficacy during treatment, perhaps guiding future dosing strategies in individual patients.…”
Section: Clinical Trialsmentioning
confidence: 99%